Comparison of the optyse lens free ophthalmoscope with the conventional direct ophthalmoscope - Van Velden, Johannes Stephanus (Division of Ophthalmology, 2014)
Includes abstract. Includes bibliographical references (leaves 42-45). Library also has copy on CD-ROM.